1995
DOI: 10.1113/jphysiol.1995.sp020682
|View full text |Cite
|
Sign up to set email alerts
|

Role of fast inhibitory synaptic mechanisms in respiratory rhythm generation in the maturing mouse.

Abstract: 1. The importance of glycinergic and GABAAergic synaptic mechanisms for respiratory rhythm generation in the maturing mouse were investigated in vivo and in an in vitro slice preparation generating respiratory rhythmic activity spontaneously at all postnatal ages. 2. The effect on respiration of topical application of strychnine or bicuculline to the surface of the ventrolateral medulla was assessed in spontaneously breathing anaesthetized mice of different ages (postnatal (P) days 0 to >56). Glycine receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0
3

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 39 publications
7
81
0
3
Order By: Relevance
“…Neverthe-less, specific compartments, which particularly include the pre-BötC, maintain their rhythmic activity in vitro [26], and such rhythmic slice preparations were extensively used to study cellular mechanisms of the primary respiratory-like rhythm generation. Previous studies showed that synaptic inhibition is functional in slices, but its contribution to the generation of the neonatal respiratory-related rhythm was considered to be marginal [21,48,49]. In that regard, our data are in full accordance with these previous studies because the in vitro rhythm never stopped after blockade of inhibitory neurotransmission.…”
Section: Technical Considerationssupporting
confidence: 93%
See 1 more Smart Citation
“…Neverthe-less, specific compartments, which particularly include the pre-BötC, maintain their rhythmic activity in vitro [26], and such rhythmic slice preparations were extensively used to study cellular mechanisms of the primary respiratory-like rhythm generation. Previous studies showed that synaptic inhibition is functional in slices, but its contribution to the generation of the neonatal respiratory-related rhythm was considered to be marginal [21,48,49]. In that regard, our data are in full accordance with these previous studies because the in vitro rhythm never stopped after blockade of inhibitory neurotransmission.…”
Section: Technical Considerationssupporting
confidence: 93%
“…One hypothesis suggests that in particular synaptic inhibition becomes more important for respiratory rhythm generation during ontogeny [9,10,20,21]. Nevertheless, synaptic inhibition is required from birth on to generate a physiological threephase motor pattern [22].…”
Section: Introductionmentioning
confidence: 99%
“…The blockage of chloride-dependent inhibition with GlyR antagonists effectively stops regular respiratory rhythmogenesis in adult animals but not in neonates (31). In contrast, the blockage of non-NMDAR in the neonate abolishes respiratory rhythm (14), while the blockage of non-NMDAR and NMDAR is required for the same effect in the adult (11).…”
Section: Discussionmentioning
confidence: 96%
“…Synaptic inhibition results in reversible and irreversible switching off of phasic activities and shaping of neuronal discharge patterns (Richter, Camerer, Meesmann & R ohrig, 1979;Richter, 1982;Ballantyne & Richter, 1986; Remmers, Richter, Ballantyne, Bainton & Klein, 1986; Anders, Ballantyne, Bischoff, Lalley & Richter, 1991;Haji, Takeda & Remmers, 1992;Klages, Bellingham & Richter, 1993;Schmid et al 1996). Blockade of GABAergic and glycinergic mechanisms by systemic or local administration of receptor antagonists greatly disturbs rhythmic respiratory functions when studied under in vivo conditions (Hayashi & Lipsky, 1992) or under in vitro conditions in slice preparations that contain more rostral medullary and pontine structures (Paton, Ramirez & Richter, 1994;Paton & Richter, 1995). These findings, however, are not consistent with reports on experiments performed in en bloc brainstem-spinal cord (Feldman & Smith, 1989;Onimaru, Arata & Homma, 1990) or medullary slice preparations lacking the pons (Ramirez, Quellmalz & Richter, 1996) showing that synaptic inhibition is not essential for the generation and maintenance of the respiratory activity.…”
mentioning
confidence: 99%